Synthesis and Characterization Mixed Ligands of Phenylalanine and Tributylphosphine Complexes with Zn(II),Cd(II) and Hg(II) Ions. (Journal of the College of Basic Education, 2022)
Complexes of Zn(II),Cd(II) and Hg(II) with mixed ligands of phenylalanine (L) and tributylphosphine (TBPh) were prepared in aqueous ethanol with (1:2:2) (M:L:TBPh). The prepared complexes were characterized using flame atomic absorption, (C.H.N) Analysis, FT.IR and UV-Vis spectroscopic methods as well as conductivity measurements. From the obtained data the octahedral structure was suggested for all prepared complexes.